Propranolol induces apoptosis of human umbilical vein endothelial cells through downregulation of CD147. (25th March 2013) - Xie, W.; Xie, H.; Liu, F.; Li, W.; Dan, J.; Mei, Y.; Dan, L.; Xiao, X.; Li, J.; Chen, X.
Summary Background Infantile haemangiomas (IHs) are benign tumours in infancy. Most patients suffering from IHs do not require treatment. However, if there is a dramatic aesthetic or functional impairment, treatment is needed. Currently the most promising therapy for complicated IHs is the oral administration of propranolol, but its mechanism is unclear. Objectives To investigate the role of CD147 in propranolol‐induced apoptosis in human umbilical vein endothelial cells (HUVECs). Methods Human umbilical vein endothelial cells were treated with propranolol, and the treatment effects were investigated through the following methodology. (i) Cell proliferation and apoptosis were detected using the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay and flow cytometric analysis. (ii) The expression level of CD147 was measured by reverse‐transcription polymerase chain reaction and Western blotting. (iii) HUVECs were transfected with lentivirus encoding CD147 short hairpin (sh)RNA or CD147 cDNA. Ensuing changes in cell proliferation and apoptosis after transfection were measured using the MTT assay and flow cytometry. (iv) The level of phosphorylation of Bcl‐2‐associated death promoter (BAD) at Ser112 in HUVECs after propranolol treatment and/or CD147 shRNA transfection was detected by Western blotting. Results Propranolol inhibited cell proliferation and induced apoptosis in HUVECs. It decreased CD147 protein expression in a concentration‐dependent manner. Knocking down CD147 not only induced apoptosis but also exacerbated the apoptosis triggered by propranolol in HUVECs. Overexpression of CD147 can protect HUVECs from apoptosis and propranolol‐induced apoptosis. Furthermore, knockdown of both propranolol and CD147 can downregulate Ser112 phosphorylation of BAD, indicating that propranolol and CD147 induce apoptosis in HUVECs through the same signalling transduction pathway. Conclusions Our studies demonstrate that propranolol‐induced apoptosis may be mediated through the downregulation of CD147 in HUVECs. This study highlights a novel step in propranolol action and suggests a potential new target for the treatment of IHs.